Analisis Inovasi Pelayanan Publik Berbasis Digital Di Dinas Komunikasi Dan Informatika Di Maluku - Mesra Rita Murni Gea; Muhamad A. Rahawarin; Ivonny Y (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The research aims to determine Digital-Based Public Service Innovations in the Communication and Informatics Office in Maluku. The data analysis used to answer the problems in this study is a qualitative descriptive analysis. Qualitative analysis with a descriptive approach. These results indicate that the Maluku government has utilized the E-government service through a website in by the communication and informatics service, namely the Maluku SIMANTAP Online E-PPID Service. E-gov services really need critical factors to ensure the success of an innovation, including; Supporting factors for the implementation of e-government-based public service innovations are: Facilities and infrastructure that support electronic-based services, positive community response by welcoming electronic-based services, support from the local government, and the leaders themselves who support application program innovations, sources Human Resources (HR). While the inhibiting factor experienced during the implementation of this e-government-based service innovation was the 'budget'.